Source sink relationship, dry matter and starch partitioning in developing ginger rhizomes during different growth stages - Krishnamurthy, K.S.; Kandiannan, K. (Journal of Plantation Crops, 2021)
Source sink relationship, dry matter and starch partitioning, rhizome bulking process in relation to dry matter and starch partitioning in developing rhizomes and growth and gas exchange parameters were studied in three popular varieties of ginger viz., IISR Varada, IISR Mahima and IISR Rejatha. Results revealed that maximum tiller production and leaf area accumulation occurred between 60 and 120 days after planting (DAP) in all three varieties. Photosynthetic rate and hormone contents (auxin and cytokinin) increased from 90-120 DAP, peaked at 120 DAP and then started declining. Biomass partitioning data revealed that the active biomass accumulation stage was between 60 and 150 DAP in ginger. The dry matter accumulation pattern in rhizomes also revealed that maximum dry matter accumulation in rhizomes also occurred between 60 and 150 DAP in all the three varieties. Maximum starch accumulation in the rhizomes also occurred during the same period. These results suggest that most of the rhizome bulking process occurred between 60 and150 DAP in ginger. Total biomass accumulation, dry matter accumulation and starch accumulation in rhizomes followed similar trends.